Motivational disturbances in rodent models of neuropsychiatric disorders - Canonica, Tara; Zalachoras, Ioannis (Frontiers in Behavioral Neuroscience, 2022)
Motivated behavior is integral to the survival of individuals, continuously directing actions towards rewards or away from punishments. The orchestration of motivated behavior depends on interactions among different brain circuits, primarily within the dopaminergic system, that subserve the analysis of factors such as the effort necessary for obtaining the reward and the desirability of the reward. Impairments in motivated behavior accompany a wide range of neuropsychiatric disorders, decreasing the patients’ quality of life. Despite its importance, motivation is often overlooked as a parameter in neuropsychiatric disorders. Here, we review motivational impairments in rodent models of schizophrenia, depression, and Parkinson’s disease, focusing on studies investigating effort-related behavior in operant conditioning tasks and on pharmacological interventions targeting the dopaminergic system. Similar motivational disturbances accompany these conditions, suggesting that treatments aimed at ameliorating motivation levels may be beneficial for various neuropsychiatric disorders.